Diagnóstico ambiental voltado a subsidiar ações de recuperação e conservação dos recursos hídricos, região da microbacia do Córrego do Meio, Reserva do Cabaçal-MT - Araujo, Mirian Braga de (2014)
In the state of Mato Grosso agricultural expansion may be responsible for the degradation of the environment, causing problems of erosion and siltation; compromising the quality of surface water, but also can destroy Permanent Preservation Areas - APPs. Due to this problem, this research aims to perform an environmental diagnosis in the watershed of the stream Medium, localized in the MT-Cabaçal Reserve, in order to support recovery actions and conservation of this watershed. The choice of this city was due to its economic and social importance for the region, because it is an area rich in scenic beauty and tourism, as well as part of the Upper Paraguay River Basin, the most important basin Pantanal. Was held in the field of recognition and delineation of the watershed area, as well as survey of Compartments morfopedológico. Five sampling points were chosen for evaluation of water quality. A survey of vegetation types throughout the watershed, which species were collected for identification in the Herbarium / UFMT was performed. 49 species belonging to 28 families were identified. Most analyzes of water present within in CONAMA Resolution 357/05 allowed, except the solids, iron, phosphorus and silica series parameters. It is concluded that the watershed lies degraded, mainly due to the change of the environment by man, by the disorderly occupation of the soil, resulting in several erosion processes, thus reducing the availability of water resources in the region.